HUMAN RIGHTS LAW FROM GENERAL THEORY OF LAW PERSPECTIVE - Spătaru-Negură, Laura-Cristiana (International Journal of Legal and Social Order, 2024)
The current study tries to analyse the relationship between the human rights law from the general theory of law perspective. Starting from the multiple meanings of the term 'law', going through the differentiation between "human rights", "public freedoms" and citizens' rights, distinguishing the component of national law and that of international law, we propose to show the readers the perspective of human rights as revealed by the general theory of human rights.